(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Understanding how the banking industry works is essential because it has ramifications across the economy. The link between bank profitability and tax planning efforts in a developing country is examined in this research. Non-financial business performance and tax preparation have also shown to have a neutral relationship, according to experts in the field. There is also no relationship between company performance and tax preparation. In particular, people examine at how corporation tax, business size, liquidity, leverage, firm age, and firm growth affect the return on assets (ROA) of India’s listed banks. The study uses data from all eight listed banks on the Indian Stock Exchange (ISE) from 2015 to 2019. For the analysis of our study, people used the ordinary least squares (OLS) regression model. There is a link between bank performance and business tax preparation, according to our findings. People urge bank CEOs to examine and manage their tax burden in order to improve their profitability.